Implementación del mantenimiento correctivo y puesta a punto del banco didáctico de hidráulica del laboratorio de mecánica de fluidos de la Universidad de América (2025)
In 2003, students Carlos Andrés Rodríguez Rodríguez and Raúl Robayo Barragán together with professor Miguel Morales carried out a degree project entitled “Design and Assembly of a generator set for the University of America”. In this project, the construction of a test bench is carried out where, using hydraulic oil and through different studies and analysis on the materials to be used according to the calculations made in characteristics such as the necessary operating pressure, the amount of oil necessary for its operation, components of the bench, among other important aspects, the respective assembly is carried out that shows the operation of a hydraulic system [1]. However, from 2003 until the completion of this project, there is only one maintenance report that refers to the change of one of the components for a renewed one with different characteristics. The fact that there are no further maintenance reports generates strong concern about the current state of the machine since there is a lack of knowledge about the conditions of all the components of the Bank, from the hydraulic and electrical equipment to the hydraulic fluid itself, causing the machine to not be in optimal conditions for use.